The everything managing people book - McClain, Gary (Everything series., 2007)
Whether you're a first-time manager or a seasoned professional, you know that a motivated, productive, and fulfilled team is your most important asset. Completely updated and revised, The Everything Managing People Book, 2nd Edition arms you with all you need to create a winning team, including straightforward advice on hiring and firing, leadership, delegation, and effective feedback.